Methodological instructions for the calculation and graphic works on the educational subject: "Machines and equipment for wells drilling, equipment for oil and gas production" - Rymchuk, D. V.; Rezvaya, K. S.; Minchukova, N. F.; Tsibulko, S. V. (National Technical University "Kharkiv polytechnic institute", 2023)
The methodological instructions were developed in accordance with the curricula and work program of the educational subject "Machines and equipment for wells drilling, equipment for oil and gas production" in the specialty 185 "Oil and gas engineering and technologies", which are in effect at the National Technical University "Kharkiv Polytechnic Institute", for students of full-time education. Methodological instructions include a set of tasks; order of tasks; samples of tasks; criteria for evaluating performance results and a list of recommended literature for preparing students for calculation and graphic works.
Keywords: methodological instructions; performing calculation and graphic work; oil and gas wells; modern technologies of drilling; educational process; tables